The potential of palm oil fuel ash as partial sand replacement in concrete - Mohamad Hafizuddin, Rasid (2017)
The consumption of natural sand taken from the river was too high due to its excessive use in concrete. The demands for this natural sand were increasing from time to time, especially on developing countries, for instance, Malaysia. Thus, the construction industries are in stress to identify alternative methods and materials to reduce the demand for natural sand. Palm oil fuel ash has been seen as one of the alternative that can replace sand in concrete mixture production and therefore could reduce the excessive production of palm oil fuel ash. In 2011, Malaysia has been reported that 5 million ha area of the land was used for oil palm plantation. This resulted in the annual production of about 61.1 million tone of solid waste such as empty fruit branches, fibres and kernels in the country. It’s also produced about 3 million tons of POFA in 2007. This situation will contribute to increasing of agro waste generated and could led to environmental issues. The main aim of this research is to study the mechanical performance of concrete containing palm oil fuel ash as partial sand replacement. The objectives of this study is to investigate the effect of unground palm oil fuel ash as partial sand replacement on workability, compressive and flexural strength of concrete. Two mix were prepared in this research which are control mix and modified mix. Where the modified mix consist various percentage of palm oil fuel ash as partial sand replacement, which are 0 to 20%. The size of the specimens that is going to be use is 100x100x100 mm (length x width x height). The specimens were subjected to water curing for 7, 28, and 60 days period. The specimens then test for workability, compressive strength test, and flexural strength test. The increase of slump value is attributed by the characteristic of POFA as low water absorption. As the POFA content increases, the slump value is increases. The slump value fall in the range of only 100mm to 120mm at water cement ratio of 0.70. The concrete mix made using POFA as partial replacement of sand showed good workability and fluidity similar to normal concrete mixes The test resulted showed that for 10% ratio of POFA in concrete, the increase in the compressive strength was about 19% compared to normal concrete. Similar results were also observed for the flexure. Conclusively, 10% of POFA is the best recommended amount to be used as partial sand replacement to produced concrete with better strength.